2013
DOI: 10.1111/adb.12039
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor mediates the suppression of alcohol self‐administration by memantine

Abstract: Brain-derived neurotrophic factor (BDNF) within the striatum is part of a homeostatic pathway regulating alcohol consumption. Memantine, a non-competitive antagonist of N-methyl-D-aspartate receptors, induces expression of BDNF in several brain regions including the striatum. We hypothesized that memantine could decrease ethanol (EtOH) consumption via activation of the BNDF signalling pathway. Effects of memantine were evaluated in Long-Evans rats self-administering moderate or high amounts of EtOH 6, 30 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 44 publications
(59 reference statements)
1
28
0
1
Order By: Relevance
“…Such an indirect and very long-lasting effect (for several weeks) of drug treatment on gene expression and relapse behaviour was recently observed by us by applying a glycine transporter inhibitor (Vengeliene et al 2010). In addition, long-lasting effects of memantine on operant behaviour (up to 30 h) has already been demonstrated in previous studies, showing that this drug may also alter gene expression and protein synthesis (Jeanblanc et al 2014;Alaux-Cantin et al 2015), and thus causing long-lasting behavioural changes. Fig.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Such an indirect and very long-lasting effect (for several weeks) of drug treatment on gene expression and relapse behaviour was recently observed by us by applying a glycine transporter inhibitor (Vengeliene et al 2010). In addition, long-lasting effects of memantine on operant behaviour (up to 30 h) has already been demonstrated in previous studies, showing that this drug may also alter gene expression and protein synthesis (Jeanblanc et al 2014;Alaux-Cantin et al 2015), and thus causing long-lasting behavioural changes. Fig.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, long‐lasting effects of memantine on operant behaviour (up to 30 h) has already been demonstrated in previous studies, showing that this drug may also alter gene expression and protein synthesis (Jeanblanc et al . ; Alaux‐Cantin et al . ), and thus causing long‐lasting behavioural changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study reported that memantine administration heightened the aggressive behavior associated with alcohol consumption (Newman et al, 2012). It is noteworthy that memantine treatments exerted the ability to reduce self-administration to alcohol (Jeanblanc et al, 2014). …”
Section: Glutamate Receptors In Audmentioning
confidence: 99%
“…Previous animal and human studies suggest that BDNF is associated with alcohol consumption (e.g., Jeanblanc, Coune, Botia, & Naassila, 2014;Jeanblanc et al, 2009). However, investigations on this association in adolescence, a risk period where alcohol consumption starts to develop to possibly problematic (ab)use (Chambers, Taylor, & Potenza, 2003), are missing.…”
Section: Introductionmentioning
confidence: 99%